Critical period of grass weed control in ALS-tolerant grain sorghum (Sorghum bicolor) is affected by planting date and environment - Contreras, Diego; Leon, Ramon G.; Post, Angela R.; Everman, Wesley J. (Frontiers in Agronomy, 2022)
Field experiments were conducted at two locations in North Carolina (Clayton and Rocky Mount) to determine the influence of row spacing and planting date on the critical period of weed control (CPWC) of grass weeds in ALS-tolerant grain. Grain sorghum was planted in May and June 2019, with either a 38 or 91 cm row spacing using an ALS-tolerant sorghum variety. Treatments consisted of “weedy” or “weed-free” plots up to 2, 3, 5, and 7 weeks after crop planting (WAP) and two control treatments of weedy and weed-free all season. Selection of grass weed species was achieved by controlling broadleaf weeds with a premix of bromoxynil plus pyrasulfutole at a rate of 264 g a.i. ha-1.Grass weeds were controlled using nicosulfuron at a rate of 69 g of a.i. ha-1. The CPWC was significantly different across locations. Row spacing and planting date factors did not influence the CPWC at Clayton. Planting date was a significant factor for the CPWC at Rocky Mount, however row spacing did not have any effect on the CPWC. Results for the CPWC are presented in terms growing degree days (GDD) from the date of crop sowing. The CPWC for grass weeds in grain sorghum at Clayton was from 368 to 849 GDD. The CPWC at Rocky Mount for May-planted grain sorghum was from 405 to 876 GDD, while the CPWC for June-planted grain sorghum ranged from 228 to 1042 GDD. These results demonstrate that cultural and environmental factors may influence the beginning, duration and end of the CPWC.